Sistem Jejaring Pelayanan Kegawat-Daruratan Kardiovaskular di Wilayah DKI Jakarta dan Sekitarnya - Surya Dharma; Anna Ulfah Rahajoe; Sunarya Soerianata (Jurnal Kardiologi Indonesia, 2012)
A tremendous progress has been made in the management of patients with ST elevation myocardial infarction (STEMI) over the last 20 years. Primary percutaneous coronary intervention (PPCI) is the preferred option for treating STEMI patients, but offering an easy, direct and fast access to this procedure is still difficult due to geographic and structural medical  services differences, especially in developing countries such as Indonesia.Analysis of Jakarta Acute Coronary Syndrome registry 2010 showed a proportion of patients not recieving acute repercusion therapy of 59% from 654 STEMI patients and majority of them  (52%) were from inter-hospital referral. The time from onset of infarction to hospital admission was more than 12 hours in almost 80% cases. Network organization is central to  optimize patient care at the acute stage of an MI and there is a strong need to build a cardiovascular care unit network system that is well organized in Jakarta. This involves a  multidisciplinary approach that should give an appropriate diagnosis and initial treatment with rapid and safe transport to a PCI capable hospital. Thus, harmonizing the activities of all hospitals in Jakarta that will give the best cardiovascular services to the community by providing two acute reperfusion therapy options (PPCI or pharmaco-invasive strategy)  depending on the time needed for the patient to reach the cath-lab.